Surgical treatment of involutional lower lid entropy - Renata Lowndes Corrêa Francalacci; Sérgio Lessa (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Entropion is defined as an internal rotation of the eyelid margin. The contact of the eyelid skin and eyelashes with the eye may result in irritating symptoms, corneal abrasions, and scars. The purpose of this study is to present the effectiveness of the technique described by Lessa in the treatment of involutional entropion. METHODS: We underwent correction of involutional entropion on 13 lower eyelids. We used the Lessa technique, in which a subciliary incision was made, a skin flap was dissected from the orbicularis oculi, a muscle strip was resected, and a skin-septum-skin suture was made. The procedure was associated with lateral support. RESULTS: There were 11 patients (5 men and 6 women) with a mean age of 76.72 years (69 to 84 years), totaling 13 eyelids, as two patients had bilateral pathology. Eight patients (9 eyelids) used muscular suspension technique. In one patient, the tarsal suspension was performed, and in two patients (three eyelids), we used the tarsal flap. The mean operative time (for eyelid) of patients undergoing muscle suspension was 36.55 min, while that in patient undergoing canthoplasty was 56 min. No patient had recurrence, and one patient developed ectropion. CONCLUSION: The technique described by Lessa proved to be effective since there was no recurrence.